Change Your Face, Change Your Life? Prison Plastic Surgery as a Way to Reduce Recidivism. (12th March 2022) - Pearl, Sharrona
Abstract: The paper explores the history and ethics of prison plastic surgery programs, which ran from the 1950s through as late as 1988 in the UK, the US, and Canada. I focus in particular on the Oakalla Prison, the Haney Young Offenders Correctional Unit, and the Kingston Penitentiary in Canada; the Huntsville Penitentiary in Texas; the Camp Hill Borstal in England; and the collaboration between Montifiore Hospital and Sing-Sing Prison in New York. Sometimes federally funded, these programs were designed to reduce rates of recidivism, operating under the notion that a changed face could lead to a changed character. The surgeries were rooted in a commitment to rehabilitation through medicine, offering participants access to surgery in exchange for good behavior, participation in an experimental protocol, and in some cases, providing training for medical students and residents. As I show, these programs were consonant with prevailing experimental and ethical ethos, and maintain deep continuity with the idea that changes in appearance could lead to changes in behavior.